2016
DOI: 10.1371/journal.pone.0168578
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Venoarterial and Venovenous Extracorporeal Membrane Oxygenation on Cerebral Metabolism in the Newborn Brain

Abstract: BackgroundExtracorporeal membrane oxygenation (ECMO) is an effective therapy for supporting infants with reversible cardiopulmonary failure. Still, survivors are at risk for long-term neurodevelopmental impairments, the cause of which is not fully understood.ObjectiveTo elucidate the effects of ECMO on the newborn brain. We hypothesized that the cerebral metabolic profile of neonates who received ECMO would differ from neonates who did not receive ECMO. To address this, we used magnetic resonance spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A retrospective review of 41 neonates after VA‐ or VV‐ECMO, who were evaluated with MRI, identified an abnormal cerebral metabolic profile suggestive of an inflammatory process and/or vasogenic edema . The authors hypothesize that these subtle differences in the brains of ECMO survivors might play a role in later neurodevelopmental impairments.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of 41 neonates after VA‐ or VV‐ECMO, who were evaluated with MRI, identified an abnormal cerebral metabolic profile suggestive of an inflammatory process and/or vasogenic edema . The authors hypothesize that these subtle differences in the brains of ECMO survivors might play a role in later neurodevelopmental impairments.…”
Section: Discussionmentioning
confidence: 99%
“…In neonates, brain metabology studies have suggested a decrease in N-acetyl-aspartate and an increase in lactic acid, which were associated with adverse neurodevelopmental outcomes. However, there was no difference in the levels of N-acetyl-aspartate and lactic acid in the bilateral basal ganglia by 1H-MRS examination after ligation ( 44 , 45 ).…”
Section: Evaluation Of the Nervous System After Reconstruction Or Lig...mentioning
confidence: 93%
“…36 Increased counts of B and T cells during ECMO indicate upregulation of the adaptive immune system, 42 which persist post-ECMO, as reflected in elevated choline levels, although whether microglia are upregulated remains unknown, making the neurologic relevance questionable. 41 Increased inflammation has also been associated with decreased autoregulation of cerebral flow, 42 further increasing the risk of hypoperfusion and ischemic stroke.…”
Section: Brainmentioning
confidence: 99%
“…39 Furthermore, poor circulation leads to spikes in proinflammatory responses and metabolic shifts. 40 Elevated creatinine levels from low clearance of metabolic byproducts, 41 along with increased lactate and localized oxygen desaturation indicate the onset of cerebral hypoxia. 36 Increased counts of B and T cells during ECMO indicate upregulation of the adaptive immune system, 42 which persist post-ECMO, as reflected in elevated choline levels, although whether microglia are upregulated remains unknown, making the neurologic relevance questionable.…”
Section: Brainmentioning
confidence: 99%